Assessment of Radionuclide Concentration and Radiation Dose in Rock in Singrauli Coalfield, India - Yadav A.K.; Sahoo S.K.; Lenka P.; Kumar A.V.; Tripathi R.M. (My University, 2025)
This study was conducted at the Singrauli coal mine environment in Singrauli coalfield, India. The activity concentrations of thorium (Th232), uranium (U238), and potassium (K40) in rock samples were analyzed by gamma spectrometry using a p-type high-purity germanium (HPGe) detector with a carbon fiber window. From terrestrial radionuclide activity concentration, the ambient radiation gamma dose rate was calculated using UNSCEAR 2000 coefficients. The average activity concentrations Th232, U238, and K40 were 77.6±38.2, 122.6±46.1, and 843.5±26.0 Bq·kg-1, respectively. The average activity ratio of Th232/U238 in various types of rocks was 1.8±0.5 Bq·kg-1. The radium equivalent activity (Raeq) for various types of rock samples varied from 132.8.1±2.8 to 382.9±6.2 Bq·kg-1, with an average value of 317.7±6.53 Bq·kg-1. The absorbed average gamma dose rate was 145±44 nGy·h-1. The annual average effective equivalent dose was 0.29±0.09 mSv·y-1. © 2019 American Society of Civil Engineers.